Improving UMKM Marketing Performance by Optimising Marketing Strategy, Creative Product Innovation and Market Orientation - Zainul Wasik; Kuncoro Catur Nugroho; Dedy Iswanto (Journal of Managerial Sciences and Studies, 2023)
Objectives - This research discusses matters relating to the marketing performance of micro and small enterprises in South Tangerang and Banten. Design/methodology/approach - Research Design This research is a survey research, with a quantitative approach, with the aim of measuring causal relationships (cause and effect).This research on the application of marketing strategies, creative product innovation, and market orientation through business development as an effort to improve marketing performance is one type of Cross Section research. To test the hypothesis, a survey will be conducted to traders in the Surabaya-Gresik area as respondents. Findings - Based on the discussion in this study, the conclusions that can be made are as follows: (1) states that creative product innovation carried out by MSMEs has a positive effect on business development. (2) states that market orientation carried out by MSMEs has no effect on business development. (3) Stating that the marketing strategy carried out by MSMEs has a positive effect on business development. (4) Stating that business development carried out by MSMEs has an effect on marketing performance